Porous silicon-based fluorescent nanoprobe for the detection of anthrax biomarker and its practical sensing applications. (November 2020) - Jung, Yuna; Kang, Sangrim; An, Jongmin; Jung, Junyang; Kim, Dokyoung
Abstract: Anthrax is an infection caused by bacterium Bacillus anthracis ( B. anthracis ), and is an old disease that poses a new threat to humans as a biological weapon. Gram-staining and polymerase chain reaction (PCR)-based assays of specimens are standard diagnostic tools for anthrax, but it is time-consuming and limited for the on-site application. In this study, we disclose a porous silicon-based nanoprobe for the detection of dipicolinic acid (DPA), which is a crucial biomarker of the anthrax spore, and its practical sensing applications. The surface of the porous silicon nanoparticles (pSiNPs) was functionalized with multiple amine arms, via a ring-opening click amination and was grafted with terbium ion (Tb 3+ ). A double antenna effect from DPA and pSiNPs to Tb 3+ was appeared dramatically and was accompanied by a significant fluorescence enhancement that had high selectivity, sensitivity, and fast response time. The resulting pSiNPs-Tb formulation was used to detect DPA in real water samples and the stimulated Bacillus subtilis ( B. subtilis ) spores. Besides, the DPA sensing application on the cellulose-based paper was successfully demonstrated as a real-time on-site sensing kit. We believe the demonstrations in this study could encourage further applications throughout a wide variety of fields. Graphical abstract: Here we describe a turn-on type fluorescent nanoprobe based on the porous silicon nanoparticles and its practical applications for the detection of the anthrax biomarker. Image 1 Highlights: A fluorescent nanoprobe for the detection of the anthrax biomarker was disclosed. The nanoprobe showed high selectivity, sensitivity, and fast response time. The nanoprobe showed real-time on-site sensing ability for the anthrax biomarker.